Water quality and degradation rate analysis: Assessing pollution and environmental impact for effective management - Nabila, Cynthia; Hendrawan, Diana Irvindiaty (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Situ Pengarengan is polluted by various types of waste from community activities and industrial sources along its shorelines. This study aims to assess the lake's degradation rate by analyzing water quality parameters and pollution sources. Method: The research was conducted from February to July 2022, with water samples collected from six sampling points. Laboratory tests measured temperature, TSS, turbidity, pH, DO, BOD, COD, nitrate, phosphate, and E. coli. The results were compared to Class 2 water quality standards under Government Regulation No. 22 of 2021. Findings: Based on IKA-NSF calculations, Situ Pengarengan's water quality is categorized as moderately polluted, with an average score of 65.04. The degradation rate coefficients for each segment are 2.21 per day, -1.07 per day, and -3.04 per day. Conclusion: The findings indicate moderate pollution levels in Situ Pengarengan, highlighting the need for improved environmental management and pollution control measures. Novelty/Originality of this Study: This study provides a quantitative assessment of Situ Pengarengan’s degradation rate using IKA-NSF calculations and degradation rate coefficients, offering a scientific basis for targeted pollution mitigation strategies.